Data for Water Services Provision in Rapidly Urbanising Villages - A Comparison of Rural and Urban Governance in Mumbai and Chennai regions in India - Haridasan, Renjitha M.; Parker, Alison; Sule, May N. (Cranfield University, 2026)
As cities grow, adjoining villages also start urbanising, adversely affecting primary services, including drinking water services. Switching to urban governance is posed as a solution for addressing this problem. We compared various dimensions of water services available to households across towns in different stages of transition in two metropolitan regions in India, to generate evidence on whether the transition of fast-urbanising villages to municipal governance results in improved water services. The data on dimensions of water services were collected through household surveys. Kruskal-Wallis test was adopted to determine if the differences found in quantitative dimensions of water services available to households across fast-urbanising villages and municipal towns were statistically significant, while a Chi-square test was employed for qualitative dimensions. Our results showed no better services in municipal towns for all dimensions studied. If some were better in municipal towns, others were better in urbanising villages under rural administration. We conclude that urban governance alone does not guarantee better services, and there are factors beyond governance contributing to improved services. The findings urge policymakers and programme implementers to look beyond the ‘transition-to-urban governance’ solution and work on institutional strengthening and context-specific approaches.
This work presents a quantitative study comparing drinking water services available to households in three types of towns in different stages of transition from rural to urban, located in close proximity : • Young Census Town (young CT): recently urbanised and under rural governance. • Old Census Town (old CT): urbanising for a longer period, still under rural governance. • Statutory Town (ST): under urban governance. From each of the two metropolitan regions of India, Mumbai and Chennai, three such towns were selected for study, resulting in a total of six towns. In addition to town-level analysis, the study also examines water services available to three settlement types within these metropolitan regions: low-income settlements, long-term resident settlements, and multi-storied apartments. Parameters and Indicators of Water Supply The data includes four principal parameters of water supply, each measured through specific indicators: 1. Accessibility -Measured by whether the principal water source is located within the household premises. -This is a nominal variable. -Additional data include the type of primary source accessed by the household. 2. Quantity of Water Available Assessed through two indicators: (i) Whether the household receives sufficient quantity for daily needs(the bare minimum scenario). (ii) Whether the household receives the required quantity whenever needed (the best-case scenario). -Both are nominal variables. -Supplementary data include reliance on supplementary sources and reasons for such dependence. 3. Regularity of Supply Measured through: (i) Average number of hours water is available per day. (ii) Average number of days water is available per week. -These are quantitative variables. -Additional insights were gathered on household water storage practices, reasons for storing water, and details of storage infrastructure. 4. Reliability of Supply -Measured as the average number of breakdowns per month. -This is a quantitative variable. Analytical Approach Hypothesis testing was employed to examine whether town type or settlement type has a significant influence on these variables. For quantitative variables, the Kruskal-Wallis test was applied. To test whether the town type has any association with the nominal variables, a Chi-square test was employed. Structure of Data Sets The analysis was conducted separately for Mumbai and Chennai, resulting in four datasets: 1. A master dataset for the Mumbai region used for descriptive analysis 2. A master dataset for the Chennai region used for descriptive analysis 3. A subset of the Mumbai master dataset used for hypothesis testing 4. A subset of the Chennai master dataset used for hypothesis testing EP/S022066/1
Keywords: Peri-urban; governance; drinking water supply